"però che solo da senso apprende" Sound perception in the Comedy - Coassin, Flavia (Spunti e Ricerche, 2016)
The essential role of sensory perception in Dante's theory of knowledge is based on the definition of human nature. Sound perception in the Divina Commedia is considered in this paper in order to illustrate the gradual process from perception to understanding. The fundamental role of sensory perception in the cognitive process is established by the unity of man, and its function is explicated in the collaboration between the senses and the intellect in the aesthetic experience; the link, as well as the initial movement towards the objects of cognition, is pleasure, which is the alpha and omega of creation, defined by Dante as an act not of necessity but one of love performed in joy.